2007
DOI: 10.1677/jme.1.02154
|View full text |Cite
|
Sign up to set email alerts
|

Growth hormone stimulates adipogenesis of 3T3-L1 cells through activation of the Stat5A/5B-PPARγ pathway

Abstract: Growth hormone-deficient (GHD) patients show a decreased number of adipocytes, which is normalized by GH replacement, indicating an adipogenic effect of GH. However, the precise mechanisms underlying this effect remain to be clarified. In this study, we investigated the adipogenic effect of GH. GH stimulated MDI (3-isobutyl-1-methylxanthine, dexamethasone, and insulin)-induced adipogenesis of 3T3-L1 cells with early induction of peroxisome proliferator-activated receptors (PPAR)g2 expression. This adipogenic e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
53
0
1

Year Published

2010
2010
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 83 publications
(57 citation statements)
references
References 62 publications
3
53
0
1
Order By: Relevance
“…Thus, it is most likely that the requirement for FBS for efficient adipogenesis correlates with the activity of Stat5. In line with this hypothesis, prolactin and growth hormone, both of which activate Stat5, are shown to promote adipogenesis in the absence/presence of FBS in 3T3-L1 and 3T3-F422A cells, respectively [19][20][21]. In this regard, the weak induction of PPARc and C/EBPa in adipogenesis at both protein and mRNA levels most likely reflects the fact that CS fails to activate Stat5s strongly with the control vector (Fig.…”
Section: Discussionsupporting
confidence: 63%
“…Thus, it is most likely that the requirement for FBS for efficient adipogenesis correlates with the activity of Stat5. In line with this hypothesis, prolactin and growth hormone, both of which activate Stat5, are shown to promote adipogenesis in the absence/presence of FBS in 3T3-L1 and 3T3-F422A cells, respectively [19][20][21]. In this regard, the weak induction of PPARc and C/EBPa in adipogenesis at both protein and mRNA levels most likely reflects the fact that CS fails to activate Stat5s strongly with the control vector (Fig.…”
Section: Discussionsupporting
confidence: 63%
“…2). Adipocytes are more than inert energy depots, and adipose tissue is a biologically active organ that carries out important (Green et al 1985;Kawai et al 2007) Antiadipogenic in primary rat preadipocytes (Wabitsch et al 1996b) and in human adipocytes (Wabitsch et al 1996a) Insulin/IGF-1 Proadipogenic Proadipogenic in 3T3-L1 cells (Green et al 1985;Smith et al 1988 Inhibitory Antiadipogenic in 3T3-L1 (Kawashima et al 1991), human marrow (Keller et al 1993), and human preadipocyte cells (Meng et al 2001) LTF Controversial No effect on 3T3-L1 adipogenesis (Hogan et al 2005;White et al 2008) Proadipogenic in 3T3-L1 cells (Aubert et al 1998) Antiadipogenic in bone marrow stromal cells (Gimble et al 1994) NP Inhibitory Antiadipogenic in 3T3-L1 cells (White et al 2008) OSM Inhibitory Antiadipogenic in 3T3-L1 cells (Miyaoka et al 2006;White et al 2008), mouse embryonic fibroblasts (Miyaoka et al 2006), and human adipose-derived mesenchymal cells (Song et al 2007) physiological processes including energy homeostasis and whole-body insulin sensitivity. Attenuating adipose tissue expansion can result in pathologies including insulin resistance.…”
Section: Discussionmentioning
confidence: 99%
“…Of note, STAT5B was unable to display similar proadipogenic properties in these nonprecursor cells (Floyd and Stephens 2003). Studies have shown that the GH-activated STAT5 proteins can induce PPARg expression in 3T3-L1 cells and C3H10T1/2 cells (Kawai et al 2007), suggesting a mechanism by which STAT5 proteins are able to promote adipocyte differentiation. Interestingly, transgenic knockout experiments have shown that disruption in either STA-T5A or STAT5B or both genes resulted in abnormal adipose tissue, and mice lacking both STAT5 proteins had fat pads one-fifth the normal size (Teglund et al 1998).…”
Section: Srebp-1mentioning
confidence: 97%
See 1 more Smart Citation
“…However, another previous study showed that expression of FAS was not affected with GH treatment at either the mRNA or protein level (Kawai et al, 2007). This difference may be due to different cell types or detection times.…”
Section: Discussionmentioning
confidence: 84%